Cerebral Hemodynamics and Executive Function in Sickle Cell Anemia. Issue 5 (12th April 2021) - Prussien, Kemar V.; Compas, Bruce E.; Siciliano, Rachel E.; Ciriegio, Abagail E.; Lee, Chelsea A.; Kassim, Adetola A.; DeBaun, Michael R.; Donahue, Manus J.; Jordan, Lori C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Individuals with sickle cell anemia experience cognitive deficits, even in the absence of cerebral infarcts or strokes. This study tested the hypothesis that elevated cerebral blood flow and oxygen extraction fraction are associated with lower executive function in individuals with sickle cell anemia. Methods: Three-Tesla brain magnetic resonance imaging was performed, including anatomic, gray matter cerebral blood flow, and global oxygen extraction fraction imaging. Executive function was measured using the working memory index from an age-appropriate Wechsler battery and tasks from the National Institutes of Health Toolbox Cognition Battery. Bivariate and multivariate models were examined (significance: P <0.05). Results: Fifty-four participants (age range=6–31 years) with sickle cell anemia were enrolled. Hematocrit was positively related to fluid cognition, cerebral blood flow was inversely related to working memory and inhibitory control, and oxygen extraction fraction was inversely related to processing speed. Associations remained significant in multivariate analyses controlling for age, income, and infarcts. Conclusions: Elevated cerebral blood flow and oxygen extraction fraction, markers of hemodynamic impairment, are associated with deficits in executive function in individuals with sickle cell anemia.